Journal clubs: Engaging clinical nurses and midwives in research - Cooper, A.; Brown, Janie (Slack Incorporated, 2018)
Â© 2018, Slack Incorporated. All rights reserved. It is essential that nurses and midwives can understand and critically evaluate research to ensure the delivery of high-quality evidence-based care. Journal clubs are an educational method that helps to develop research capacity and assist with bridging the gap between research and clinical practice. To maintain competence and remain current with the latest evidence, a commitment to continuing professional education is required. This article describes how a successful journal club led to clinical nurses identifying a gap in their own practice, which resulted in a research project being conducted by the members of the journal club.